2021
DOI: 10.3390/genes12060871
|View full text |Cite
|
Sign up to set email alerts
|

TOMM40 RNA Transcription in Alzheimer’s Disease Brain and Its Implication in Mitochondrial Dysfunction

Abstract: Increasing evidence suggests that the Translocase of Outer Mitochondria Membrane 40 (TOMM40) gene may contribute to the risk of Alzheimer’s disease (AD). Currently, there is no consensus as to whether TOMM40 expression is up- or down-regulated in AD brains, hindering a clear interpretation of TOMM40’s role in this disease. The aim of this study was to determine if TOMM40 RNA levels differ between AD and control brains. We applied RT-qPCR to study TOMM40 transcription in human postmortem brain (PMB) and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Indeed, translocase of outer mitochondrial membrane 40 ( TOMM40 ), which lies in linkage disequilibrium with the APOE gene, has previously been reported to be associated with Alzheimer’s disease [ 37 ]. A recent study reported an association between elevated TOMM40 RNA levels and decreased mitochondrial copy number as well as mitochondrial membrane potential in oxidative stress-challenged cells [ 38 ]. However, clarification of the mechanisms underlying the interaction between APOE4 and TOMM40 awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, translocase of outer mitochondrial membrane 40 ( TOMM40 ), which lies in linkage disequilibrium with the APOE gene, has previously been reported to be associated with Alzheimer’s disease [ 37 ]. A recent study reported an association between elevated TOMM40 RNA levels and decreased mitochondrial copy number as well as mitochondrial membrane potential in oxidative stress-challenged cells [ 38 ]. However, clarification of the mechanisms underlying the interaction between APOE4 and TOMM40 awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to TOMM40 being commonly connected with AD; we excluded the studies that were solely focused on the prediction of dementia outcomes, and studies specifically included patients with AD diagnoses. Current RNA quantification methodologies have limited capability to distinguish between TOMM40 mRNA and its pseudogenes [ 13 ]. Due to this reason, studies that focused purely on TOMM40 RNA may generate contradicting results.…”
Section: Methodsmentioning
confidence: 99%
“…As the powerhouse of the cell, the function of mitochondria determines the efficacy of metabolic and signaling pathways. Recent studies demonstrated that elevated TOMM40 mRNA expression is associated with fold changes in mitochondria membrane potential (Δψm), mitochondrial DNA (mtDNA) copy number, respiratory rate, and ATP production [ 12 , 13 ]. Mitochondrial functions are tightly regulated, and their dysfunctions can be associated with disease pathogeneses.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent results based on gene haplotypes have shown a strong influence of the regulated expression of the gene in the brain [ 79 ]. Similarly, several association studies have shown mixed results regarding the association of TOMM40 (outer mitochondrial membrane translocase 40) with AD and the dysregulation of mitochondrial function independent of ApoE4 [ 80 , 81 ], but a recent haplotype study showed differences between TOMM40 haplotypes encoding ApoE4 and ApoE3 in the association probability for AD [ 82 ].…”
Section: The Genetics Of Admentioning
confidence: 99%